Analgesia administration by sex among pediatric emergency department patients with abdominal pain - Marie E. Vastola; Bryn E. Mumma; Jeffrey R. Fine; Daniel J. Tancredi; Joshua W. Elder; Angela F. Jarman (JEM Reports, 2024)
Background: There is conflicting data about sex-based differences in the treatment of acute pain in the ED. Little is known about sex-based disparities in analgesia in pediatric ED patients. Objectives: Our objective was to determine whether analgesic administration rates differ between female and male pediatric patients presenting to the ED with abdominal pain. Methods: We conducted a retrospective cohort study of ED patients 5–21 years old with abdominal pain between 6/1/19 and 6/30/21. The primary outcome was receipt of any analgesia, and secondary outcomes were receipt of opioid analgesia and time to receipt of analgesia. Multivariable regression models were fitted for each outcome. Results: We studied 1087 patients; 681 (63%) were female with a median age of 17 years (IQR 13, 19) and 406 (37%) were male with a median age of 14 years (IQR 9, 18). 371 female patients (55%) and 180 male patients (44%) received any analgesia. 132 female patients (19%) and 83 male patients (20%) received opioid analgesia. In multivariate analyses, female patients were equally likely to receive any analgesia (OR 1.30, 95% CI 0.97–1.74, p ​= ​0.07), but time to analgesia was 14% longer (GMR 1.14, 95% CI 1.00–1.29, p ​= ​0.04). Non-White patients were 32% less likely to receive opioids (OR 0.68, 95% CI 0.47–0.97, p ​= ​0.04). Conclusions: Female pediatric ED patients were equally likely to receive any analgesia as male patients, but their time to analgesia was longer. Non-White patients were less likely to receive opioid analgesia than White patients.